2018
DOI: 10.1007/s00421-018-4008-7
|View full text |Cite
|
Sign up to set email alerts
|

Whole body cryotherapy, cold water immersion, or a placebo following resistance exercise: a case of mind over matter?

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 50 publications
2
35
1
2
Order By: Relevance
“…Although participants in the present study were not informed of the study hypothesis and a control intervention was used for comparison, we did not examine the potential influence of the placebo effect on the observed responses. Accumulating evidence indicates that therapeutic effects of popular recovery modalities, such as cryotherapy, stem at least partially from a placebo effect (53,54). These important observations emphasize the need for future studies on the effects of HT to implement an effective placebo-controlled design.…”
Section: Discussionmentioning
confidence: 99%
“…Although participants in the present study were not informed of the study hypothesis and a control intervention was used for comparison, we did not examine the potential influence of the placebo effect on the observed responses. Accumulating evidence indicates that therapeutic effects of popular recovery modalities, such as cryotherapy, stem at least partially from a placebo effect (53,54). These important observations emphasize the need for future studies on the effects of HT to implement an effective placebo-controlled design.…”
Section: Discussionmentioning
confidence: 99%
“…CWI, primarily as a result of its ability to decrease tissue temperature and blood flow (Gregson et al 2011;Costello et al 2012;Gregson et al 2013;Mawhinney et al 2013;Mawhinney et al 2017a;Mawhinney et al 2017b), has been suggested to reduce delayed onset muscle soreness (Leeder et al 2012;Roberts et al 2014;Hohenauer et al 2015) and muscle oedema/swelling (Yanagisawa et al 2003;Yanagisawa et al 2004;Vaile et al 2008;Roberts et al 2014), improve recovery of muscle function/performance (Vaile et al 2008;Vaile et al 2011;Versey et al 2013;Roberts et al 2014) and increase gene expression of molecular markers of endurance exercise adaptation (Ihsan et al 2014;Joo et al 2016;Allan et al 2017). However, it is important to note that not all studies show beneficial effects of CWI on markers of postexercise recovery (Paddon-Jones & Quigley, 1997;Goodall & Howatson, 2008;Versey et al 2013;Wilson et al 2019). A recent meta-analysis reported that the proposed beneficial effects of CWI on postexercise recovery seem to be based more upon subjective rather than objective (blood) markers (Hohenauer et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological benefits of WBC in athletes have been attributed to cold-induced analgesia, reduction of muscle temperature, and suppression of inflammation-derived RONS and cytokines. Studies into the effects of a cold therapy on exercise performance and recovery have reported diverse outcomes ranging from beneficial [11][12][13] through negligible [14][15][16][17] to negative ones [18,19]. Roberts et al [19] indicated that post-exercise cold water immersion could even attenuate acute anabolic signaling and long-term adaptation of muscular system to exercise.…”
Section: Introductionmentioning
confidence: 99%